Phytoplankton cell size control can be affected by photosynthetic light energy utilization - Li, Wanzhu; Wang, Baoli; Xiao, Jing; Yang, Meiling; Xu, Sheng; Liu, Cong-Qiang (Frontiers in Microbiology, 2022)
Phytoplankton cell size is well known as an essential functional trait, but its control factors are still unclear. Considering light provides the necessary energy for phytoplankton survival, we hypothesized that photosynthetic light energy utilization could influence phytoplankton cell size control. Several scenarios were conducted to understand the relationship between Fv/Fm and cell size for phytoplankton interspecies, and metatranscriptome in the field and transcriptome in the laboratory were used to understand relevant molecular mechanisms. The results indicated that there was a universal significant positive relationship between Fv/Fm and cell volume in general. The molecular evidence demonstrated that light utilization by phytoplankton regulates their cell size by harmonizing the generation and allocation of chemical energy and fixed carbon in the cell. Phytoplankton cell size would cease to enlarge once the increased light energy conversion and subsequent fixed carbon could no longer satisfy the increasing demand of size enlargement. This unity of energy and matter in shaping phytoplankton size results in cell size being an important functional trait. This study is the first to discover the above molecular mechanisms and is helpful to deepen the understanding on the cell size control of phytoplankton.